The Impact of Concomitant Medication Use on Patient Eligibility for Phase I Cancer Clinical Trials - Borad, Mitesh J. (Ivyspring International Publisher, 2012)
Concomitant medication (CM) use may result in Phase I cancer clinical trial ineligibility due to concern for potential CM-investigational drug interactions or alteration of investigational drug absorption. Few studies have examined the impact of CM use on trial eligibility. Methods: We reviewed records of 274 patients on Phase I trials at a single academic institution. Demographics, CM identities and classes, CM discontinuation, reasons, and incidence of CM substitution were recorded. CM-investigational drug cytochrome P450 (CYP) enzyme interactions were documented. Statistical analysis was performed using descriptive statistics. Results: 273 of 274 patients (99.6%, 95% confidence interval [CI] 98.9-100%) took CM, with a median of 8 CM per patient (range 0 - 42). CM discontinuation occurred in 67 cases (25%, 95% CI 19-30%). The most common CM classes discontinued were herbal (17 cases, 25%, 95% CI 16-37%) and proton pump inhibitors (15 cases, 22%, 95% CI 12-32%). CM discontinuation reasons were: protocol prohibition (32 cases, 48%, 95% CI 36-60%); potential CM-investigational drug interaction (25 cases, 37%, 95% CI 26-49%); other (10 cases, 15%, 95% CI 6-23%). A potential CM-investigational drug CYP interaction was noted in 122 cases (45%, 95% CI 39-50%). CM potentially weakly decreased investigational drug metabolism in 52 cases (43%, 95% CI 34-51%), and potentially strongly decreased investigational drug metabolism in 17 cases (14%, 95% CI 8-20%). Investigational drug potentially weakly decreased CM metabolism in 39 cases (32%, 95% CI 24-40%), and potentially strongly decreased CM metabolism in 28 cases (23%, 95% CI 15-30%). CM substitution occurred in 36/67 cases (54%, 95% CI 41-66%) where CM were discontinued to allow for eventual participation in clinical trials. Overall in 2 cases (0.7%, 95% CI 0.1-2.6%), patients were protocol ineligible because CM could not be discontinued or substituted. Conclusions: This study highlights the high prevalence of concomitant medication use among cancer patients enrolled in phase I clinical trials. Most patients did meet trial eligibility criteria with careful substitution and discontinuation of CM. The most common reason for discontinuation of CM was protocol prohibition. The most common medications discontinued were herbal, proton pump inhibitors, selective serotonin reuptake inhibitor anti-depressants, and non-steroidal anti-inflammatory drugs.